Collection and Recycling of Solid Urban Waste: Contribution to Debate Ambiental Sustentability - Almeida, Giovana Goretti Feijó de; Silveira, Rosí Cristina Espindola da; Engel, Vonia (Future Studies Research Journal: Trends and Strategies, 2020)
Purpose – To reflect on the selective collection of solid urban waste and what causes unrestrained consumption to society without considering the disposal of the products it consumes. Theoretical framework – The theoretical framework is structured based on the approach to planning policy in the scope of urban solid waste and discussions on lifestyles and environmental education based on the consumption and disposal of urban solid waste. At the end, we present the case of solid urban waste, in Santa Cruz do Sul-RS. This research also discusses how the selective collection and the recycling process of solid urban waste are guided in the context of environmental planning policies, in the municipality of Santa Cruz do Sul-RS, in the period from 2013 to 2016, and from the term of the Municipal Plan for Integrated Solid Waste Management - PMGIRS. Design/methodology/approach – The method is a case study with qualitative research, including secondary data from IBGE, PMGIRS, PERS and SNIS. Questionnaires were applied to SMMASS; Conesul and COOMCAT. Findings – The educational-environmental issue is also a strategy to face the problems related to the recycling of solid urban waste. Although laws have been passed since 2010, only current legislation is still insufficient. Society lacks interest in the correct disposal of urban waste, which reveals indifference to those who work in recycling (waste pickers). It is important to work with quality of life in order to promote local and regional development. Research, Practical & Social implications – The importance of working with environmental awareness in the selective collection of solid waste, together with socio-environmental issues from an early age, through an educational stance, as well as the understanding that we are all co-responsible for what society produces and discards. Originality/value – It focuses on discussions on selective collection with a view to recycling solid urban waste, in Santa Cruz do Sul-RS, from the perspective of local and regional development.